Advanced high-affinity glycoconjugate ligands of galectins - Hovorková, Michaela; Červený, Jakub; Bumba, Ladislav; Pelantová, Helena; Cvačka, Josef; Křen, Vladimír; Renaudet, Olivier; Goyard, David; Bojarová, Pavla (Bioorganic chemistry, 2023)
Galectins are proteins of the family of human lectins. By binding terminal galactose units of cell surface glycans, they moderate biological and pathological processes such as cell signaling, cell adhesion, apoptosis, fibrosis, carcinogenesis, and metabolic disorders. The binding of monovalent glycans to galectins is usually relatively weak. Therefore, the presentation of carbohydrate ligands on multivalent scaffolds can efficiently increase and/or discriminate the affinity of the glycoconjugate to different galectins. A library of glycoclusters and glycodendrimers with various structural presentations of the common functionalized N-acetyllactosamine ligand was prepared to evaluate how the mode of presentation affects the affinity and selectivity to the two most abundant galectins, galectin-1 (Gal-1) and galectin-3 (Gal-3). In addition, the effect of a one- to two-unit carbohydrate spacer on the affinity of the glycoconjugates was determined. A new design of the biolayer interferometry (BLI) method with specific AVI-tagged constructs was used to determine the affinity to galectins, and compared with the gold-standard method of isothermal titration calorimetry (ITC). This study reveals new routes to low nanomolar glycoconjugate inhibitors of galectins of interest for biomedical research.
Keywords: sacharidy; galektiny; Ligands; Glycoconjugates; Humans; Polysaccharides; ligandy; glykokonjugáty; polysacharidy; lidé; Carbohydrates; Galectins